Leveraging process mining from a Lean Six Sigma perspective - Taouil, Fatima Ezzahra; Martínez, Felipe; Vlasov, Vladyslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This research aims at exploring how Process Mining can enhance or not Lean Six Sigma methodologies in improving the blocked orders management process at Company X. This will be done by comparing standalone LSS against an integrated approach with PM.
Vedoucí práce: Felipe Martínez
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses